INVESTIGATION THE INTEREST OF CREDITOR AND DEBTOR IN SUSPENSION OF DEBT PAYMENT OBLIGATIONS - Kautsar, Izzy Al; Muhammad, Danang Wahyu (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThe purpose of this research is to determine what interests underlie debtors in proposing debt settlement through PKPU institutions and to analyze the legal position of separatist creditors in the PKPU process. This study uses a juridical normative research method by utilizing the statutory regulatory approach. An alternative way to settle debt payment obligations for debtors is by submitting a suspension of debt payment obligations. The essence of using this institution is to direct the parties in carrying out debt restructuring. In theory, the use of the suspension of debt payment obligation (PKPU) will protect the interests of the parties effectively and fairly. But in practice, this PKPU institution became ineffective and was only used by one party to achieve its own interests. Including the interests of separatist creditors which are limited through SKMA 3/KMA/SK/I/2020, it is implied that there is an injustice for the separatist creditors in submitting PKPU submissions, then the Supreme Court issued SKMA 3/KMA/SK/IV/2020 which revoked the previous regulation while providing legal protection for separatist creditors in the PKPU process. The result of this research is that the debtor's interest in PKPU submission is 1. That debtor wants to restructure its debt 2. Debtor is no longer able to compete with the market. It was also found that the settlement of PKPU cases could be faster than the time period provided by Law 34/2007. Separatist creditors must be included in the PKPU settlement process, because their voting rights will determine the outcome of the agreement and the interests of creditors in a fair and balanced manner, in addition to debt settlement through PKPU institutions based on article 222 Law 34/2007 there is no difference in criteria for creditors.Keywords: creditors; debtors; suspension of debt paymentAbstrakTujuan dari penelitian ini adalah untuk menentukan kepentingan apa saja yang mendasari debitor dalam mengajukan pemberesan utang melalui lembaga PKPU dan menganalisa kedudukan hukum kreditur separatis dalam proses PKPU. Penelitian ini menggunakan metode penelitian normatif yuridis dengan memanfaatkan metode pendekatan peraturan perundang-undangan. Jalan alternatif dalam penyelesaian pembayaran kewajiban utang bagi debitor adalah dengan cara mengajukan penundaan kewajiban pembayaran utang. Inti dari penggunaan lembaga ini untuk mengarahkan para pihak dalam melakukan restrukturisasi utang. Secara teori penggunaan lembaga penundaan kewajban pembayaran utang(PKPU) akan melindungi kepentingan para pihak secara efektif dan adil. Tapi pada praktiknya, lembaga PKPU ini menjadi tidak efektif dan hanya dimanfaatkan oleh salah satu pihak untuk mencapai kepentinganya sendiri. Termasuk kepentingan kreditur separatis yang dibatasi melalui SKMA 3/KMA/SK/I/2020, tersirat bahwa terjadi ketidakadilan bagi kreditur separatis dalam melakukan pengajuan PKPU, kemudian Mahkamah Agung mengeluarkan SKMA 3/KMA/SK/IV/2020 yang mencabut aturan sebelumnya sekaligus memberikan perlindungan hukum bagi kreditur separatis dalam proses PKPU. Hasil dari penelitian ini adalah bahwa kepentingan debitor dalam pengajuan PKPU adalah 1. Bahwa dirinya ingin melakukan restrukturisasi utang 2. Sudah tidak mampu lagi bersaing dengan pasar. Ditemukan pula dalam penyelesaian perkara PKPU bisa lebih cepat dibandingkan periode waktu yang diberikan oleh UU 34/2007. Kreditur separatis harus diikutsertakan dalam proses penyelesaian PKPU, karena hak suaranya akan menentukan hasil kesepakatan dan kepentingan para kreditur secara adil dan seimbang, selain itu dalam pemberesan utang melalui lembaga PKPU berdasarkan pasal 222 UU 34/2007 tidak ada perbedaan kriteria pada kreditur.